AUTOMAÇÃO E PRECARIZAÇÃO DA FORÇA DE TRABALHO DOS BANCÁRIOS: a experiência do Banco do Brasil a partir dos anos 1990 - Carvalho, Roosevelth Ramos Barroso (2015)
This scientific production was developed in order to present a study on the process automation and the precariousness of banking workforce since the 1990s in most state-owned company of the domestic financial sector, the Bank of Brazil. Since the 1990s, the Bank of Brazil has experienced successive changes of administrative and operational nature, which form a complex program of systematic adjustments by neoliberal policies and deepened by the Restructuring of the XXI century. And contemplating the measures taken, we are downsizing process of staff, agencies closing and deliberate mobilization. These, among other measures, were the ones that caused significant impact on the banking sector. Such measures represent a break from the values established between the bank and its employees, redefining principles of labor relations that supported these relationships at other times. For these analyzes, we used the methodological approach of Marxist nature, realized through an approach based on historical dialectic materialism. Thus, in order to achieve the objectives proposed herein, starting from an understanding of the dynamics which includes the reproduction of the Brazilian banking workforce, focusing on categories of primary and secondary analyzes, highlighting automation, precarious, work, productive restructuring, bank. In addition, the study aims to analyze how the introduction of automation in the Bank of Brazil, while being presented as something advantageous to the bank itself, its efficiency and for customers, in reality nothing more than a strategy used by employers to appropriate more profit and paying lower wages. That is, instead of this process strengthen labor relations, under the guise of a more productive and efficient service, has worsened the situation of the banking worker in the late twentieth century and early twenty-first century with the strengthening of the productive restructuring, which materialized supported the dismantling of labor rights.